3D Hierarchically Mesoporous Zinc-Nickel-Cobalt Ternary Oxide (Zn0.6Ni0.8Co1.6O4) Nanowires for High-Performance Asymmetric Supercapacitors - Ahsan, Muhammad Tayyab; Usman, Muhammad; Ali, Zeeshan; Javed, Sofia; Ali, Rashad; Farooq, Muhammad U.; Akram, Muhammad Aftab; Mahmood, Asif (Frontiers in Chemistry, 2020)
Increased efforts have been devoted recently to develop high-energy-density supercapacitors (SC) without renouncing their power efficiency. Herein, a hierarchically mesoporous nanostructure of zinc-nickel-cobalt oxide (ZNCO) nanowires (NWs) is constructed by hierarchical aggregation of ZNCO nanoparticles is reported. It is worth noting that cobalt and nickel rich lattice imparts higher charge storage capability by enhanced reversible Faradaic reaction while zinc provides structural stability and higher conductivity. Moreover, particulate nature of ZNCO NWs allows deep diffusion of electrolyte thus enabling reversible charge storage under higher current densities. The as-prepared ZNCO NWs exhibited excellent specific capacitance of 2082.21 F g-1 at the current density of 1 A g-1 with high stability up to 5000 charge-discharge cycles. Further, the asymmetric SC device was assembled using ZNCO NWs (ZNCO NWs//MWCNTs) which exhibited high energy density of 37.89 Wh kg-1 and excellent capacitance retention up to 88.5% over 1000 cycles. This work presents ways to construct multi-component high-energy-density materials for next-generation energy storage devices.